SEDIMENT TRANSPORT AND CAUSE OF THE DEPOSITION IN NAI LAGOON (NINH THUAN PROVINCE) - Vinh, Vu Duy; Huong, Do Thi Thu; Quan, Nguyen Van; Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2016)
This paper presents some studies on the characteristics of sediment transport and morphological change in the Nai lagoon (Ninh Thuan province). The 3D model was established based on Delft3D system combining hydrodynamics - wave - sediment transport and the MORFAC (the morphological acceleration factor) approach method with 36 different scenarios. The study results show that sediment flux in the coastal zone is predominantly moving from the east-northeast to the west-southwest directions. The sediments coming from the sea into the Tri Thuy channel are very big as compared with output sediment flux from the lagoon with daily average value of 760.1 m3/day and 122.8 m3/day respectively; these are the main cause of Nai lagoon inlet’s deposition processes. On the other hand, input and output sediment fluxes at the lagoon inlet (Tri Thuy Bridge) are small with daily average value of 3.4 m3/day and 2.1 m3/day respectively. The sediment from different sources into the Nai lagoon, but very small amount transported to the sea is the main cause of the deposition in Nai lagoon with rate of 5 - 15 mm/year. The sediment flux from the lagoon to the sea in the flooding is small and mostly kept in the lagoon. Therefore, the flooding makes significant increase of deposition rate in Nai lagoon.